2014
DOI: 10.4236/oalib.1100659
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Violence and Associated Factors among Rural High School Female Students, in Hadiya Zone, Southern Nation and Nationalities Peoples’ Region, Ethiopia, 2013

Abstract: The objective of this study is to assess violence and associated factors among rural high school female students in Hadiya zone, Ethiopia. A school based cross-sectional quantitative study was employed. Multistage sampling technique was used to select study subjects. Self administered questionnaires were used to collect the data and study was conducted on 801 rural high school female students in Hadiya Zone from March 25 to April 25/2013. The overall percentage of physical, sexual or psychological violence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 10 publications
6
25
1
Order By: Relevance
“…The lifetime prevalence of gender-based-violence among female students was in agreement with other previous studies conducted in Ethiopia and the pooled estimated prevalence of gender-based violence among adolescents attending higher educations in sub-Saharan African countries [12,[15][16][17][18]. For example, a cross-sectional study conducted to assess the prevalence and factors associated with gender-based-violence among high school students residing in rural areas of Hadiya zone in Ethiopia reported 62.2% [15]. Further, a recent systematic review and metaanalysis that investigated the prevalence of gender-basedviolence among female students attending schools in sub-Saharan Africa also showed a much similar report [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lifetime prevalence of gender-based-violence among female students was in agreement with other previous studies conducted in Ethiopia and the pooled estimated prevalence of gender-based violence among adolescents attending higher educations in sub-Saharan African countries [12,[15][16][17][18]. For example, a cross-sectional study conducted to assess the prevalence and factors associated with gender-based-violence among high school students residing in rural areas of Hadiya zone in Ethiopia reported 62.2% [15]. Further, a recent systematic review and metaanalysis that investigated the prevalence of gender-basedviolence among female students attending schools in sub-Saharan Africa also showed a much similar report [16].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of GBV before joining the school, after joining the school and during the current academic year were 355 (58.8%), 288 (47.7%) and 254 (42.1%) respectively. The lifetime prevalence of gender-based-violence among female students was in agreement with other previous studies conducted in Ethiopia and the pooled estimated prevalence of gender-based violence among adolescents attending higher educations in sub-Saharan African countries [12,[15][16][17][18]. For example, a cross-sectional study conducted to assess the prevalence and factors associated with gender-based-violence among high school students residing in rural areas of Hadiya zone in Ethiopia reported 62.2% [15].…”
Section: Discussionsupporting
confidence: 88%
“…A total of 40,409 participants with 11,511 cases of lifetime sexual violence were included in the analysis. The prevalence ranged from 4.30 to 76.40% [11, 12, 31–34, 36–51]. The pooled estimate prevalence of lifetime sexual violence was 26.22% [95%CI 19.48–33.57%].…”
Section: Resultsmentioning
confidence: 99%
“…In five studies, researchers investigated the prevalence of emotional violence and this ranged from 26.1 to 50.8% [33, 34, 3638]. A total of 4486 study participants with 1038 cases of emotional violence were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is concerning that there are so many high school students without knowledge about dating violence. I have not found any research on victims of dating violence that is limited to Japanese high school students, but a survey on Ethiopian female high school students showed that 62.2% had suffered physical, sexual, and mental violence [8]. An American survey revealed that 9.44% of 12-year-old high school students (all ethnicities) had suffered physical violence from a partner.…”
Section: Discussionmentioning
confidence: 99%